Carotid Artery Stenosis in Diabetic Patients Presenting With Acute Ischemic Stroke - Wishhal Sundar; Lubna Shafi; Rakesh Panjwani; Sameeta; Tahreem Shafi; Ahsan Ashfaq (ziauddin University, 2020)
Background: Stroke is the commonest life-threatening neurological disorder. The Abnormal narrowing or stenosis of the Carotid Artery is a major determinant of ischemic stroke in diabetic patients. The main objective of study was to estimate the frequency of carotid artery stenosis in diabetic patients presenting with acute ischemic stroke. Methods: This was a Cross-Sectional study conducted at Medicine wards Jinnah Post-Graduate Medical Centre, Karachi from 5th December 2014 to 5th June 2015. Total 101 patients were included. During the hospitalization, patients were subjected to carotid Doppler ultrasonography to assess carotid artery stenosis. Patients were provided routine medical care during the hospitalization. Data was analyzed using SPSS v23.0. Chi-Square was used to analyze the differences between the categories. The p-value of <0.05 was considered as significance. Results: Total 101 patients were included in the study. There were 71.8% males and 28.2% females. The mean age was 53.7±10.2 years. On analysis of risk factors, it was observed that 59% patients had hypertension, 34.2% patients were obese, 34.2% patients had dyslipidemia, 51.3% patients had history of smoking. On analysis of carotid artery stenosis among the diabetics, it was observed that 20.8% diabetics had carotid artery stenosis. Conclusion: Stenosis of Carotid artery was common in patients suffering from acute ischemic stroke and diabetes mellitus. Among modifiable risk factor in patients with stroke having carotid artery stenosis, Hypertension was most common whereas fasting blood sugar FBS level greater than 100 g/dl lead to increased chances of having carotid artery stenosis.